2016
DOI: 10.1186/s12939-016-0391-z
|View full text |Cite
|
Sign up to set email alerts
|

Access to free or low-cost tuberculosis treatment for migrants and refugees along the Thailand-Myanmar border in Tak province, Thailand

Abstract: BackgroundIn Tak province, Thailand migrants and refugees from Myanmar navigate a pluralistic healthcare system to seek Tuberculosis (TB) care from a variety of government and non-governmental providers. This multi-methods qualitative study examined access to TB, TB/HIV and multidrug-resistant tuberculosis (MDR-TB) treatment with an emphasis on barriers to care and enabling factors.MethodsIn the summer and fall of 2014, we conducted 12 key informant interviews with public health officials and TB treatment prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 9 publications
(20 reference statements)
0
54
0
Order By: Relevance
“…Our results suggest that in Tak province access to TB treatment is related to legal status [14]. Migrants who have enrolled in the Thai Compulsory Migrant Health Insurance Scheme are eligible to access low cost TB treatment at the Thai government hospital.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results suggest that in Tak province access to TB treatment is related to legal status [14]. Migrants who have enrolled in the Thai Compulsory Migrant Health Insurance Scheme are eligible to access low cost TB treatment at the Thai government hospital.…”
Section: Resultsmentioning
confidence: 99%
“…Collecting verbal consent allowed us to further safeguard participants’ identities, as we could avoid carrying around documentation with the names of informants. We have detailed our research methods elsewhere [13, 14]. This paper reports on the findings from the interviews and FGDs that are relevant to TB control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this might a barrier to access healthcare and getting proper medical checkup for migrant workers while being suspected of TB infection. This is supported by the study of Tchirhart, et al [36] which reported that insurance, and access to free or low-cost services were major factors affecting access to health care system among migrant TB patients. Moreover, migrant TB patients are in serious need of health system response along the Thailand-Myanmar border [37].…”
Section: Discussionmentioning
confidence: 59%
“…Migrant participants described their ablity to seek care as linked to the financial and non financial resources required to travel and undergo treatment. Patients identified language of services, availability of free or low cost services, and psychosocial support as important health system characteristic that affect accessibility [18].…”
Section: Access Transportation To Health Servicesmentioning
confidence: 99%